Multilevel inverter based on cascaded association of Buck EIE inverters. Issue 6 (1st July 2013) - Costa, Natalia; Melo, Fernando; de Freitas, Luiz; Coelho, Ernane; Freitas, Luiz C.G.
Abstract : The multilevel inverters are pointed in the literature as one of the most suitable solutions for high‐power applications, in medium and high voltage levels. These inverters are based on the association of converters, either in parallel or in series, aiming at processing smaller amount of the total output power in each converter. Generally, the output voltage and/or current are a staircase waveform and the output voltage has low harmonic distortion because of the used passive filters and/or modulation techniques. In this context, a novel approach on cascaded multilevel inverters is presented in this study. The proposed topology is based on the cascaded association of Buck EIE inverters, developed from the EIE active commutation cell. The output voltage is totally controlled and it follows a desired reference signal, which assures a low harmonic distortion without the necessity of using passive filters on the output of the converter. The level of voltage stress over the power semiconductor devices, especially switches and diodes, are kept low even for high voltage applications. Detailed circuit description is given as well as a complete theoretical analysis. The mathematical model for the three‐level Buck EIE inverter is also presented and, in order to confirm the operation of the proposed topology, experimental results are here addressed.